(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is devoted to the actual problem of young people’s attitudes to religion, and considers its identification. Attitude of today’s youth to religion is considered as the level of knowledge of the content of religion and the degree of personal acceptance. The paper reveals how the correlation between universal and private religion takes place. The results of empirical research are revealed, despite the rise of religiosity among young people, spontaneous initiation to its rites and unformed ideas about religious faith exist. Substantial change of ethno-confessional balance, socio-economic difficulties, catastrophic in nature is considered. Key words: modern youth, religion, education, identification, faith, the role of religion and culture.